Penerapan Digital Marketing Bagi Pemasaran Produk Kelompok Pemberdayaan Kesejahteraan Keluarga - Pradiptya, Adhi; Kusumawati, Citra Andriani; Ariefiantoro, Teguh (Universitas Negeri Gorontalo, 2025)
The transformation of digital technology has affected the world of marketing, which directly helps MSMEs in increasing the effectiveness of business operations. However, the lack of skills and knowledge of the community, especially housewives in Tlogosari village in marketing their products, make the products not sold optimally. This community service program aims to help MSMEs adopt the use of digital technology in increasing the effectiveness of business operations. The community service program was conducted in the form of training for PKK groups in Tlogosari Kulon Village, Semarang City. The results of the activity showed that the PKK group experienced an increase in knowledge and use of digital marketing. This can be seen from the average results of pre-test and post-test, which shows that the increase in knowledge and understanding of MSMEs in the use of digital marketing is 97,3%. Therefore, this training is important to improve product marketing and attract consumers.